Topical application of highly concentrated water-in-oil emulsions: Physiological skin parameters and skin penetration in vivo - A pilot study - Binder, Lisa; Klang, Victoria; Sheikh Rezaei, Safoura; Neuer, Olivia; Zhang, Ziwei; Lunter, Dominique Jasmin; Wolzt, Michael; Valenta, Claudia (International journal of pharmaceutics, 2019)
Important aspects in the development of new dermal drug delivery systems are the formulations' physicochemical properties and stability. Moreover, their influence on skin physiology and their penetration performance in vivo are of crucial interest. We have recently developed novel concentrated water-in-oil emulsions based on a non-ionic silicone surfactant; the present study deals with the effect of these formulations on physiological skin parameters of healthy volunteers after repeated application. Variations in skin condition and barrier integrity were investigated using classical biophysical and spectroscopic techniques. After four weeks of continuous treatment, no signs of skin irritation could be observed. Both tested emulsions had a positive effect on skin properties despite their relatively high water content and low lipid content. In vivo tape stripping studies revealed penetrated amounts of the incorporated model drug fluorescein sodium of almost 50% of the applied dose, with a superior performance of emulsions with isopropyl myristate when compared to liquid paraffin. In summary, our study confirmed the suitability of the developed W/O emulsions for pharmaceutic and cosmetic applications. [Display omitted]